Tanto Ella Assume Novitate al Fianco. Lisboa, Turim e o intercâmbio cultural do século das luzes - Isabel Ferreira da Mota (Investigação, 2019)
This volume provides an interdisciplinary, multifaceted view of a key period of the making and remaking of the European artistic, cultural and political landscape at the turn from the eighteenth to the nineteenth century. It focus on the relationships between Lisbon and Turin as a prime analyzer of the main forms of sociability and circulation of objects, knowledge, tastes, styles of government and public policies upon which a new European geopolitical panorama was erected, extending as well to the overseas territories. The variety of approaches deployed in the volume are unified by a broad notion of cultural history which includes on an equal footing the visual and the scientific, the material and the political culture. The studies in this volume underline the crucial importance of the transfer of tastes and habitus, and the associated emergence of new forms of sensibility, in shaping the transition from Enlightenment to the Post-Napoleonic Europe.